Photoluminescence enhancement study in a Bi-doped Cs2AgInCl6 double perovskite by pressure and temperature-dependent self-trapped exciton emission. Issue 5 (14th January 2022) - Dave, Kashyap; Huang, Wen-Tse; Leśniewski, Tadeusz; Lazarowska, Agata; Jankowski, Dawid; Mahlik, Sebastian; Liu, Ru-Shi
Abstract : We have used a halide precursor acid precipitation method to synthesize Cs2 AgIn1− x Bi x Cl6 microcrystals and achieved internal quantum efficiency of 52.4% via self-trapped exciton emission. Abstract : Here, we report a halide precursor acid precipitation method to synthesize Cs2 AgIn1− x Bi x Cl6 ( x = 0, 0.02, 0.04, 0.08, 0.16, 0.32, 0.64, and 1) microcrystals. Cs2 AgInCl6 and Bi derivative double perovskites show broadband white light emission via self-trapped excitons (STEs) and have achieved the highest internal quantum efficiency of up to 52.4% at x = 0.08. Synchrotron X-ray diffraction confirmed the linear increase of lattice parameters and cell volume with Bi 3+ substitution at In 3+ sites. Absorbance, photocurrent excitation, and photoluminescence excitation spectra are used to observe possible transitions from the valence to the conduction band or free exciton (FE) states as well as transitions within local Bi 3+ states. The broadband photoluminescence is quenched via a single nonradiative process with an activation energy Δ E = 1490 cm −1 for Cs2 AgIn0.92 Bi0.08 Cl6 . Under normal conditions, we observed STE emission, but applying external pressure alters the electronic structure such that at elevated pressure, the only emission via the FE state is observed. We anticipate that structure, temperature and pressure-dependent photoluminescence studies will help the future use of a single-source lead-free double perovskite for white light-emitting diode applications.